Menganalisis Pertumbuhan Ekonomi di Kabupaten Banggai: Identifikasi Sektor Unggulan dan Dampaknya terhadap Pembangunan Daerah: Analyzing Economic Growth in Banggai Regency: Identifying Leading Sectors and Their Impact on Regional Development - Ali, Rendi Pranata (Jurnal Ilmiah Produktif, 2024)
This study aims to identify the leading sectors within the economic structure of Banggai Regency. Utilizing secondary data, specifically the Gross Regional Domestic Product (GRDP) at constant prices for Banggai Regency and Central Sulawesi Province from 2019 to 2023, the analysis employs Economic Growth techniques, Shift-Share analysis, and Location Quotient (LQ) analysis. The findings indicate that the information and communication sector exhibits the highest growth rate compared to other sectors. Additionally, the economic growth rate of Central Sulawesi significantly influences the economic structure growth in Banggai Regency. The growth rate of Banggai Regency's economy is relatively robust and positively impacts the broader economic structure of Central Sulawesi Province. However, Banggai Regency currently lacks a comparative advantage that could enhance its regional economy. The primary sectors identified within Banggai Regency's economic structure include mining and quarrying, agriculture, forestry and fisheries, and real estate, while other sectors are categorized as non-basic.